Employee Performance Evaluation System for Work Effectiveness at the Bone and Transmigration Office of the District of Bone Regency of South Sulawesi, Indonesia. - Hilaluddin, Mahmud; Hamzah, Dedi; Herman; Salhudin; Mawiah, A.Tanda (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2020)
This research was conducted at the Regional Inspectorate of Bone Regency. This study aims is to determine and analyze employee performance appraisal at the Bone and Transmigration Office of the District of Bone. As well as to find out and analyze the effectiveness of the work of employees at the Department of Manpower and Transmigration Bone Regency. To uncover these problems, the sampling in this study was purposive sampling. For data collection methods of observation, interviews and questionnaires were used. Analysis of the data used is a Likert scale by finding the average frequency (mean) and total average frequency (total mean). The results showed that the employee performance appraisal system at the Department of Manpower and Transmigration of Bone Regency was largely determined by the knowledge, skills, attitudes, behavior of leadership. The effectiveness of the work of employees at the Office of Manpower and Transmigration Bone Regency is determined by the work skills possessed.